2019
DOI: 10.1136/ijgc-2019-000669
|View full text |Cite
|
Sign up to set email alerts
|

Burden of lymphatic disease predicts efficacy of adjuvant radiation and chemotherapy in FIGO 2018 stage IIICp cervical cancer

Abstract: ObjectiveNodal involvement is one of the most important prognostic factors in cervical cancer patients. We aimed to assess the prognostic role in relation to the burden of nodal disease in stage IIICp cervical cancer.MethodsData on all consecutive patients diagnosed with cervical cancer undergoing primary surgery (radical hysterectomy plus lymphadenectomy) or neoadjuvant chemotherapy followed by radical hysterectomy plus lymphadenectomy, between January 1980 and December 2017, were collected in a dedicated dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
12
1
Order By: Relevance
“…All of the patients in our cohort had SCRT. It was satisfactory to have a 5-year OS of 92% for patients with T 1 N < 3 pLN in our cohort, which was comparable to that in the STARS study (23) and studies from Bogani et al (14) and Tim et al (25). From this point, radical surgery followed by SCRT was a reasonable treatment option for this group of patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…All of the patients in our cohort had SCRT. It was satisfactory to have a 5-year OS of 92% for patients with T 1 N < 3 pLN in our cohort, which was comparable to that in the STARS study (23) and studies from Bogani et al (14) and Tim et al (25). From this point, radical surgery followed by SCRT was a reasonable treatment option for this group of patients.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, Tsai et al (13) reported that patients with only one pLN had achieved similar outcomes compared to pN0, and patients with ≥ 2 pelvic pLNs had lower survival rates (87% vs. 61%, p < 0.001) than those with pN0. In the study from Bogani et al (14), median disease-free survival was 100, 42, and 12 months for patients with one, two, and three or more positive node(s), respectively. Kwon et al evaluated a group of 249 cervical cancer patients treated in 13 Korean institutions (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent publications show that having multiple affected nodes at diagnosis is associated with a higher risk of development of nodal failure in LACC (34,35). In the EMBRACE I cohort we found that having affected nodes in multiple nodal regions was a strong risk factor for NF in descriptive analysis.…”
Section: Discussionmentioning
confidence: 54%
“…Chemotherapy uses anticancer drugs to destroy or inhibit the growth of cancer cells. It is one of the most effective treatments that improve cancer survival, and it can be given before and/or after surgery, either alone or in combination with other treatments, such as hormones [ 1 ], radiation [ 2 ], and immunotherapy [ 3 ]. However, intracellular delivery of anticancer drugs is hindered by their hydrophobicity and low molecular weight.…”
Section: Introductionmentioning
confidence: 99%